2023
DOI: 10.3390/plants12030675
|View full text |Cite
|
Sign up to set email alerts
|

LG5, a Novel Allele of EUI1, Regulates Grain Size and Flag Leaf Angle in Rice

Abstract: Grain size and flag leaf angle are two important traits that determining grain yield in rice. However, the mechanisms regulating these two traits remain largely unknown. In this study, a rice long grain 5 (lg5) mutant with a large flag leaf angle was identified, and map-based cloning revealed that a single base substitution followed by a 2 bp insertion in the LOC_Os05g40384 gene resulted in larger grains, a larger flag leaf angle, and higher plant height than the wild type. Sequence analysis revealed that lg5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Short chains, that is, A + B1, showed a decreasing trend and long chains, that is, B2 + B3, showed an increasing trend under salt stress conditions. The results were in agreement with Li et al (2023), who reported an increase in the levels of short-chain molecules, a decrease in the levels of long-chain molecules can lead to the destabilization of the double helix structure. When the percentage of short amylopectin chains (A and B1 chains) increases, it creates a higher likelihood of bonding and molecular interactions (Li et al, 2018).…”
Section: Effects Of Salt Stress On Fine Structure Of Rice Starchsupporting
confidence: 92%
“…Short chains, that is, A + B1, showed a decreasing trend and long chains, that is, B2 + B3, showed an increasing trend under salt stress conditions. The results were in agreement with Li et al (2023), who reported an increase in the levels of short-chain molecules, a decrease in the levels of long-chain molecules can lead to the destabilization of the double helix structure. When the percentage of short amylopectin chains (A and B1 chains) increases, it creates a higher likelihood of bonding and molecular interactions (Li et al, 2018).…”
Section: Effects Of Salt Stress On Fine Structure Of Rice Starchsupporting
confidence: 92%
“…The mean value for days to owering for all genotypes were 102.412 days ( (Jallow et al, 2023), Grain size is de ned by the length of each grain, while grain shape is de ned by the proportion between grain length and breadth (Li et al, 2023).…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…The semi-quantitative PCR program included an initial denaturation at 94°C for 3 minutes (1 cycle), followed by denaturation at 94°C for 1 minute, annealing at 51°C for 55 seconds, extension at 72°C for 55 seconds, and a nal extension at 72°C for 10 minutes. 10µl PCR product was taken from each cycles (21,24,27,30,35) to assess the expression level of the rice grain quality related genes. The PCR products were then loaded onto a 2% agarose gel along with 100bp DNA ladder, and the ampli ed products were documented using a gel documentation system (Alpha Inotech, UVI Tech).…”
Section: Pcr Cycle Steps and Pcr's Ampli Cation Productsmentioning
confidence: 99%
“…Basmati rice are classi ed in slender grain but it classi ed into extralong slender grain when the L/B ratio is ≥ 3 (Khurana and Kumar, 2023), aromatic non-basmati genotype classi ed into short medium grain and non-aromatic genotype classi ed into medium slender grain. Grain size and grain shape are strong rice quality criterion which is seen rstly by consumers (Jallow et al, 2023), Grain size is de ned by the length of each grain, while grain shape is de ned by the proportion between grain length and breadth (Li et al, 2023).…”
Section: Table3 Mean Performance Of Morphological and Physical Charac...mentioning
confidence: 99%